Pengaruh Model Pembelajaran POE (Predict-Observe-Explain) Berbantuan Media Gerugi (Gerak Perubahan Energi) terhadap Pemahaman Konsep IPA tentang Energi pada Siswa Kelas IV - Adella Rosalyta; Zulmi Roestika Rini (Departement of Mathematics Education, 2024)
The study aims to find out the impact of the Predict Observe Explain (POE) learning model on the understanding of concepts. This type of research is quasi-experimental design in the form of nonequivalent control group design. The population in this study is all the students of SD Negeri Jepat Lor 01. Sampling technique uses non-probability sampling techniques taken purposively. The sample of the research is class IVA and IVB SD State Jepat Lor 01. The data collection techniques in this research are test and non-test techniques. Test techniques use pretest and posttest while non test techniques use observation, lifting and documentation. Data analysis techniques with normality tests, homogenity tests, one way anova tests, simple linear regression tests, and independent sample t tests. The results of the study showed: (1) There was a difference in student's understanding of concepts versus the use of POE assisted media Gerugi, demonstrated with a degree of significance of 0,006 and 0,001 < 0,05 using the independent sample t test and one way anova test (2) There was an influence of the usage of the POE Assisted Media Gerugi model on the ability to understand concepts, proven with the degree of importance of 0,000<0,05 using simple linear regression test.